Effect of Clopidogrel on Thrombin Generation in Platelet-Rich Plasma in the Rat - Hérault, J.-P.; Dol, F.; Gaich, C.; Bernat, A.; Herbert, J.-M. (Thrombosis and Haemostasis, 1999)
Clopidogrel (25 mg/kg, p.o.), a potent and selective inhibitor of ADP-induced platelet aggregation, significantly inhibited, in the presence of platelets, ex vivo thrombin generation triggered by low concentrations of tissue factor. Clopidogrel reduced the area under the curve (23%, p <0.05) and the thrombin peak concentration (35%, p <0.05) but did not affect the lag phase of thrombin generation. Under the same experimental conditions, heparin (100 μg/ml) inhibited thrombin generation mostly by delaying and by reducing the burst of thrombin. In a stasis-induced venous thrombosis model in rats under low thrombogenic challenge, clopidogrel inhibited thrombus formation (ED50 = 7.9 ± 1.5 mg/kg, p.o. – n = 10), confirming the existence of a close relationship between platelet activation and thrombin generation leading to blood coagulation and venous thrombosis.